Multiple Lines of Evidence for Independent Origin of Wild and Cultivated Flowering Cherry (Prunus yedoensis) - Cho, Myong-Suk; Kim, Seung-Chul (Frontiers in Plant Science, 2019)
As with many other ornamental and cultivated plants that have been under human selection and cultivation for a long time, it has been a major challenge to trace back the complex evolutionary history of flowering cherry, Prunus yedoensis. This challenge has been further amplified by great morphological similarities, little molecular divergence, frequent natural and artificial hybridization, and poor documentation of breeding history among cultivated and wild flowering cherries. The origin and taxonomic distinction between wild P. yedoensis from Jeju Island, Korea, and one of the most popular cultivated flowering cherries, P. × yedoensis ‘Somei-yoshino’ has been a controversy for the past few decades. We sampled many areas extensively, and using four different molecular markers we provided evidence for their independent origin. Wild P. yedoensis in Korea originated from multiple bidirectional hybridization events between two sympatric species, P. spachiana f. ascendens as the maternal species and P. serrulata var. spontanea/P. serrulata var. quelpaertensis as the most probable paternal species. On the contrary, our results supported a single artificial hybrid origin of P. × yedoensis ‘Somei-yoshino’ from cultivated P. spachiana f. ascendens as the maternal species and P. speciosa, a species endemic to Izu Islands, as the paternal species. Based on extensive sampling, we provided strong evidence that wild and cultivated P. yedoensis are distinct taxonomic entities that have originated from different evolutionary processes. A potential for the development of new cultivars from wild P. yedoensis and conservation of diverse germplasms in situ insular setting and ex situ should be explored in the future.